Profanity Language in Megan The Stallion's Song Lyrics - Elsa Gustryansar (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
ABSTRACT This research aimed to analyze the categories and the function of profanity language in Megan Thee Stallion’s song lyrics by using Andersson Sociolinguistic Theory. This research used Descriptive Qualitative Method. The source of the data in this research is Thot Shit, Savage, and Hot Girl Summer song lyrics by Megan that is published in 2020. The data was collected through listening the song while reading the lyrics as whole part, Identifying the profanity language to the song, Taking notes from the lyrics that show of profanity language in Thot Shit, Savage, and Hot girl Summer song, and Classifying the categories and function of profanity language in Megan Thee Stallion’s song lyrics. This research is analyzed by presenting the data that contain of profanity language in Thot Shit, Savage, and Hot Girl Summer song lyrics, Describing the context of situation of the data, Interpreting the data based on the types and function of profanity language in Megan Thee Stallion’s song lyrics, and Drawing the conclusion. The result of this research shows that most or almost all of the profane expressions in Megan’s song lyrics are dominated in profanity categories. The category of profanity words includes curse and scorn conveyed on the other person, here the interlocutor who hears the words of Megan’s song can feel insulted because they humble themselves and defame someone. Profanity language in Megan’s song lyrics consists of Expletive Profane, Abusive Profane, Humorous Profane, and Auxiliary Profane. Keyword: Sociolinguistic, Taboo Words, Swear Words, Profanity